Comparing the Higher Order and Lower Order Learning Factors in the Cognitive Domain Learning Attainments of Students - Das, Rajib Lochan; Miah, Titu; Puttimanoradeekul, Papob; Toyn, Phawadee Thongnopkhun (IUBAT Review, 2026)
This research investigates the variances in the attainment of students in the cognition levels: lower-order learning (LOL) and higher-order learning (HOL). This is important because it helps improve teaching methods tailored to the discipline. The cognitive domain of Bloom’s Taxonomy has six layers: the first three – remembering, understanding, and applying – are considered LOL, while the other three – analysing, evaluating, and creating – are regarded as HOL. The primary focus of this research is on student learning—specifically how it varies when exposed to different levels of cognitive demand in various disciplines. Teaching strategies are considered only as they influence learning outcomes. To compare students' learning under LOL and HOL, an answer was sought to the question, "Does the students' learning vary by LOL and HOL in diverse disciplines?" The study intricate 340 undergraduate students enrolled in five selected courses of five programs of various disciplines in Bangladesh and Thailand. HOL achievements were always strongly and positively dependent on those in LOL. Learning patterns among students aged 22-26 years were found to be similar. The study can be used by academicians as its findings provide evidence for comparing data between LOL and HOL of the students, which can notify educators to balance the cognitive levels in their efforts to make them employable and lifelong learners. IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 217-238